Combined effects of temperature and interspecific competition on the mortality of the invasive garden ant, Lasius neglectus: A laboratory study. (April 2017) - Frizzi, Filippo; Bartalesi, Viola; Santini, Giacomo
Abstract: The invasive garden ant, Lasius neglectus, is a dominant species due to its capacity to form large supercolonies. This species was assumed to possess a wide thermal niche since it is able to adapt to cold climates, which is a factor that boosted its rapid expansion from south to many central-northern European Countries. However, the effect of variations in environmental temperatures on its competitive ability against other species has still not been investigated. In this paper, we analyzed the change in survival ability of Lasius neglectus during encounters with two Mediterranean dominant ants ( Crematogaster scutellaris and Tapinoma nigerrimum ) at four different temperatures (15, 20, 25 and 30 °C). Firstly, control tests were performed to provide the baseline survival ability of the three species at different temperatures. Secondly, competition tests were carried out at the same temperatures. Lasius neglectus survival was negatively affected by high temperature (30 °C) in control tests, and this impairment was much more pronounced in competition tests. On the contrary, the two opponent species were only marginally affected by temperatures in control tests. Crematogaster scutellaris was a better competitor than L. neglectus, particularly at high temperatures. Tapinoma nigerrimum was a weaker competitor and was always outcompeted by L. neglectus, particularly at low temperatures. This result could suggest that L. neglectus is at a disadvantage during interspecific encounters when temperatures are high and that the predicted future increase in environmental temperatures may potentially enhance this handicap. Highlights: The effect of environmental temperature and competition on three ants is investigated. Competitive ability of the invasive Lasius neglectus is lower at higher temperature. Mediterranean species are negatively affected by low but not by high temperatures. Climate change may influence the spread of this invasive species.